Austrian immigration to Canada : selected essays - Szabo, Franz A. J. (Carleton University Press, 1996)
This collection of nine essays originated in a symposium on Austrian immigration to Canada held at Carleton University in May 1995. Held in conjunction with the larger Austrian immigration to Canada research project, initiated to mark the Austrian millennium in 1996, the conference brought together European and Canadian scholars from several disciplines. The full range of immigrant and refugee experience in Canada is addressed: culture, politics, demographics, identity, language, memory, hardship and achievement.